Pemberdayaan Masyarakat Desa Dalam Pencegahan Dan Penanggulangan Kebakaran Lahan Di Desa Hilir Mesjid Kabupaten Barito Kuala: (Studi Pembentukan Barisan Pemadam Kebakaran Swadaya Masyarakat Di Kota Banjarmasin) - Ifrani Ifrani; Fathul Achmadi Abby (Scholar Center, 2022)
ABSTRACT During the last few years, the high number of forest and land fires in the dry season requires preparedness and faster action, especially in areas close to the village communities. So that with the participation and empowerment of rural communities through training and mentoring, the formation of the Self-Subsistent Fire Fighter Community is believed to reduce the number of land fires significantly. The villagers of Hilir Mesjid are a community that is emotionally attached to one another with a sense of kinship that is still close as a characteristic of the Traditional Community. So that the willingness of the community to participate in overcoming land fires in the vicinity is still high. However, the absence of infrastructure and knowledge of technology for preventing and overcoming forest and land fires has made the potential of the Self-Subsistent Fire Fighter Community for the Hilir Mesjid Village not empowered optimally.This community service proposal is one of the efforts to maximize the potential of the Self-Subsistent Fire Fighter Community through integration with the